THE MECHANISM OF METHODOLOGICAL IMPROVEMENT OF PROFESSIONAL AND PEDAGOGICAL COMPETENCE OF FUTURE MEDICAL TEACHERS - Feruza K. Iskandjanova (Central Asian Journal of Medicine, 2022)
Professional competence is a person's ability to perform professional duties. Professionalism is made up of many professional competencies. Competence includes the ability to use these skills depending on their knowledge, skills and abilities. In the context of deepening the content of pedagogical and information technologies, the key to the success of any doctor-teacher in the field of professional activity is an approach to the methodological improvement of his professional, pedagogical and information competence.